2007
DOI: 10.1177/0145482x0710100705
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Assistive Technology and Teacher Preparation Programs for Individuals with Visual Impairments

Abstract: Parker et al. (1990) reported that teachers of students with visual impairments and deaf-blindness had poor or nonexistent knowledge of specific areas of assistive technology, and a study by Mack, Koenig, and Ashcroft (1990) on computer training of students with visual impairments concluded that teacher education programs have an obligation to train teachers in the necessary knowledge, skills, and motivation to provide a bridge between students and technology. A recurring theme of the four studies of the assis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 8 publications
0
22
0
3
Order By: Relevance
“…Lack of assistive technology knowledge and skills are not a novel discovery. Previous researchers (Ashton et al, 2005;Bausch and Hasselbring, 2004;Parette et al, 2006;Smith and Kelley, 2007;Wilcox et al, 2006 ) concluded that teachers were not confident in using assistive technology due to lack of knowledge and training in this area. Knowledge and skills of using assistive technology essential for general education and special education teachers in equal measure.…”
Section: Resultsmentioning
confidence: 99%
“…Lack of assistive technology knowledge and skills are not a novel discovery. Previous researchers (Ashton et al, 2005;Bausch and Hasselbring, 2004;Parette et al, 2006;Smith and Kelley, 2007;Wilcox et al, 2006 ) concluded that teachers were not confident in using assistive technology due to lack of knowledge and training in this area. Knowledge and skills of using assistive technology essential for general education and special education teachers in equal measure.…”
Section: Resultsmentioning
confidence: 99%
“…Görme yetersizliği olan birey görsel bir imgeyi tamamen kavrayamazken normal gören bireyler de doğuştan görme yetersizliği olan bir insanın yarattığı haptik bir imgeyi anlamada güçlük çekerler (Zatta ve Pullin, 2004). Görme yetersizliği olan bireyler kendi dünyasını düzenleme ve anlayabilme için mutlaka haptik duyumunu kullanmalıdır ve bunun için (Bishop ve Barraga, 2004;Cox ve Dykes, 2001;Bülbül ve Eryılmaz, 2012;Nepomuceno vd., 2016;Okcu ve Sözbilir, 2019;Özyürek, 1998;Smith ve Kelley, 2007)…”
Section: Introductionunclassified
“…Holmes et al (2008) consider that teachers of visually impaired students need to understand and implement the use of the latest assistive technology. Despite the almost non-existent research conducted in Portugal in the field of visual impairment, international studies indicate that teachers of visually impaired students do not have enough training on technologies that are relevant to this area (Abner and Lahm 2002;Kapperman et al 2002;Smith and Kelley 2007;Zhou et al 2011). This lack of specific training is "more severe for teachers in the regular classroom" (Papadopoulos and Goudiras 2005, p. 75), than for special education teachers.…”
Section: Introductionmentioning
confidence: 99%
“…This lack of specific training is "more severe for teachers in the regular classroom" (Papadopoulos and Goudiras 2005, p. 75), than for special education teachers. According to Smith and Kelley (2007) the use of ICT by students depends on teachers initial and continuous training acquired, however the deficit of teacher training is often cited as the leading barrier to the implementation of ICT in educational practices (Ribeiro et al 2010). Despite the obvious weaknesses of teacher training, studies indicate that they believe in the potential of ICT as promoters of inclusive education (Alves et al 2009;Benigno et al 2007).…”
Section: Introductionmentioning
confidence: 99%